EFFECT OF TOTAL QUALITY MANAGEMENT AND JUST IN TIME ON PRODUCTION COST EFFICIENCY IN PT SEMEN PADANG - Mike Kusuma Dewi; Elsa Meirina (LPPM Press STIE Indragiri Rengat, 2020)
The application of Total Quality Management (TQM) is closely related to the quality of existing resources in the company. TQM provides a foundation for quality management and is an alternative in ensuring customer satisfaction, as well as Just In Time (JIT) which is a comprehensive and comprehensive production system. inventory management system where raw materials are purchased and produced as much as needed and used at the right time in every production process. In this study, the authors will examine the effect of TQM and JIT in efficiency of production costs at the manufacturing company PT Semen Padang in period 2016-2019. The data collection method was carried out by distributing questionnaires to each unit manager at PT Semen Padang which included managers of the accounting unit, human resource unit and production unit. The sampling technique used purposive sampling method and there were 67 samples. The analytical method used is to use the classical assumption test. Data analysis was also performed using the multiple regresion method with the SPSS Ver.16 application Based on the results of the hypothesis testing, it shows that Total Quality Management (TQM) has a positive effect on cost efficiency and Just In Time (JIT) has a positive effect on cost efficiency.